2020
DOI: 10.1038/s41598-020-60307-9
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzee Coordination and Potential Communication in a Two-touchscreen Turn-taking Game

Abstract: Recent years have seen a growing interest in the question of whether and how groups of nonhumanprimates coordinate their behaviors for mutual benefit. On the one hand, it has been shown that chimpanzees in the wild and in captivity can solve various coordination problems. on the other hand, evidence of communication in the context of coordination problems is scarce. Here, we investigated how pairs of chimpanzees (Pan troglodytes) solved a problem of dynamically coordinating their actions for achieving a joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Fundamental questions that arise in relation to comparative research is which human abilities to perform joint actions are shared with other species and what their evolutionary roots may be. Joint action abilities in great apes, our evolutionary ancestors, may have driven the evolution of communication as a way to achieve enhanced abilities to pursue joint action goals (Voinov et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Fundamental questions that arise in relation to comparative research is which human abilities to perform joint actions are shared with other species and what their evolutionary roots may be. Joint action abilities in great apes, our evolutionary ancestors, may have driven the evolution of communication as a way to achieve enhanced abilities to pursue joint action goals (Voinov et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Chimpanzees cooperate (Mitani, 2009), but not much is known about the ways in which they coordinate their joint efforts. In experimental settings, some chimpanzees used location enhancing behaviors (e.g., bodily positioning, touching, peering) (Melis and Tomasello, 2019), or generic gestures (e.g., arm fling, clapping, banging on panels; Voinov et al 2020) to entice their conspecific partners into a joint action. In natural contexts, chimpanzees and bonobos communicate to coordinate joint actions like joint travel (Fröhlich et al, 2016) and social play (Heesen et al, 2017;Hobaiter and Byrne, 2014), yet "… the degree to which these actions are joint in terms of whether or not partners aim to achieve shared goals together, or whether partners have shared intentions, remains unknown."…”
Section: Discussionmentioning
confidence: 99%
“…Although there are more studies examining cooperation and coordination abilities in great apes, our focus here is only in those studies that either report or specifically investigated communication aimed at coordination with the partner. scenario Crawford [44] juvenile chimpanzees Menzel [45] chimpanzees: adult male-female infant Chalmeau [46] mother-offspring orangutans Völter et al [47] chimpanzees: adult male-male juveniles Schweinfurth et al [48] attention-getters between conspecifics (distal set-up) various pairs of unrelated chimpanzees Voinov et al [49] vocalizations and tactile recruitment of human partner (partners in the same space) young female chimpanzee-human experimenter…”
Section: (A) Common Informationmentioning
confidence: 99%
“…Future studies should investigate this possibility in more detail. More recently, Voinov et al [49] also introduced a coordination breakdown scenario and found gestural communication among chimpanzees interacting in a two-touchscreen turn-taking game. In this task, chimpanzees are required to send a virtual target from one screen to another using two touch screens for mutual benefit.…”
Section: (A) Common Informationmentioning
confidence: 99%
See 1 more Smart Citation